ナンキョクイキ ニオケル クモ・ヒョウセツケン ノ ホウシャ コウカ - 山内, 恭; ヤマノウチ, タカシ; Yamanouchi, Takashi (1997)
P(論文) 地球放射収支観測計画(ERBE)による衛星データおよび地上放射観測データ等から, 南極域における氷床, 海氷および雲の放射収支に対する影響を論じた結果を紹介する。大陸氷床は, アルベドに寄与すると共に, その高度によって地表面温度に, そして外向き長波長放射(OLR)に影響を与えている。気候の仕組みの中で重要なフィードバック効果を示す海氷は, 大気外アルベードを増加, OLRを減らす。雲の作用より海氷の働きは小さいように見えるが, この海氷の影響は雲が現状の分布をしている下でのものであり, 海氷独自の効果はもっと強く, 雲の効果に匹敵する。雲が海氷の効果をマスクしているわけである。昭和および南極点基地で, 衛星による大気上端での放射収支と, 地上観測からの放射収支が比較された。定着海氷域および内陸氷床上での地表面, 大気および大気上端での雲の放射効果(強制力)として導出された。 Examination of the effects of clouds, ice sheet and sea ice on the radiation budget in the Antarctic using Earth Radiation Budget Experiment (ERBE) data were reported. The continental ice sheet affects not only the albedo, but also the surface temperature because of elevation, and hence the OLR. Sea ice, which is a critical climate feedback factor, appears to have less impact on radiation than do clouds. However, these surfaces lie underneath clouds, and it was found that the independent effect of sea ice is as large as that of clouds, and clouds are masking the radiative effect of sea ice by more than half. The radiation budget at the top of the atmosphere from satellite observation and that at the surface from the surface radiation measurements at Syowa and South Pole Stations were compared. Cloud radiative forcing at both stations for the surface, atmosphere and top of the atmosphere was derived. departmental bulletin paper